Topologized Soft Fundamental Group of Soft Topological Group - Kadhem, Hiyam Hassan; Jawad, Noor Abdul Moneem (Iraqi Journal of Science, 2020)
In this paper, we show that each soft topological group is a strong small soft loop transfer space at the identity element. This indicates that the soft quasitopological fundamental group of a soft connected and locally soft path connected space, is a soft topological group.